Presentative Constructions in English and Lithuanian - Kahėdaitė, Violeta (Kalbotyra, 2002)
The article focuses on the type of existential sentence which is known in linguistic literature as a presentative construction. This type is distinguished on functional grounds: its communicative function is to introduce a new entity into a discourse. In addition, presentative structures exhibit different syntactic and distributional behaviour from that which is evident in the existential sentence. In Lithuanian scholarly writings the presentative type is referred to as ‘introductory’ or ‘existential’; however, no systematic treatment of the issue is available in the literature. The article advances arguments for the need to distinguish a corresponding presentative construction in Lithuanian and offers a linguistic description of the basic characteristics of the structure under discussion.